A new diagnostic index for sarcopenia and its association with short‐term postoperative complications in patients undergoing surgery for colorectal cancer. (4th February 2019) - Yang, J.; Zhang, T.; Feng, D.; Dai, X.; Lv, T.; Wang, X.; Gong, J.; Zhu, W.; Li, J.
Abstract: Aim: Sarcopenia is a robust prognostic indicator of outcomes after surgery for colorectal cancer (CRC). However, there are no serum markers routinely available for estimating skeletal muscle mass (SMM). The present study aimed to describe a new sarcopenia index (SI), serum creatinine (Scr) × cystatin C‐based glomerular filtration rate, and investigate its association with short‐term complications after curative resection of CRC. Method: Consecutive patients who underwent curative resection of CRC from December 2011 to January 2017 were retrospectively identified. Skeletal muscle cross‐sectional area was analysed on L3 computed tomographic images. Receiver operating characteristic curve analysis showed that the cutoff points of SI for sarcopenia were below 56.1 in men and below 43.7 in women. Patients were classified into low and high SI groups in accordance with these cutoff values. The association between SI and body composition and the impact of preoperative SI on postoperative outcomes were analysed. Results: Among 417 patients, SI showed a stronger correlation with skeletal muscle area (SMA) ( r  = 0.537, P  <   0.001) than with the Scr/cystatin C ratio ( r  = 0.469, P  <   0.001) and Scr ( r  = 0.447, P  <   0.001). The low SI group had a lower SMA, lower preoperative haemoglobin, a higher prevalence of sarcopenia and experienced more postoperative complications compared with the high SI group (all P  <   0.001). Multivariate logistic regression analysis showed that the independent risk factors for overall complications were low preoperative haemoglobin, low SI, sarcopenia and American Society of Anesthesiologists grade ≥ 3. Conclusion: This new SI is a simple and useful surrogate marker for estimating SMM, and is associated with outcomes after CRC surgery.